Solving Inhomogeneous Linear Partial Differential Equations (Journal of Partial Differential Equations, 2020)
Lagrange's variation-of-constantsmethod for solving linear inhomogeneous ordinary differential equations (ode's) is replaced by amethod based on the Loewy decomposition of the corresponding homogeneous equation. It uses only properties of the equations and not of its solutions. As a consequence it has the advantage that it may be generalized for partial differential equations (pde's). It is applied to equations of second order in two independent variables, and to a certain system of third-order pde's. Therewith all possible linear inhomogeneous pde's are covered that may occur when third-order linear homogeneous pde's in two independent variables are solved.
Keywords: Partial differential equations; linear differential equations; inhomogeneous differential equations